Effects of land use change on discharge of the Paraíba do Sul river - Capozzoli, Caluan Rodrigues; Cardoso, Andrea de Oliveira (Ciência e Natura, 2021)
The Paraíba do Sul river basin is located in the southeast region of Brazil and across São Paulo, Rio de Janeiro and Minas Gerais states. In addition to the urban and rural population in the basin, Paraíba do Sul River supplies about twelve million people in the Metropolitan Region of Rio de Janeiro, the third-largest metropolitan region in South America. Land-use in the basin is predominantly dairy farming, where inadequate soil management has affected the quality and quantity of water in the basin. In this work, a distributed hydrological model was performed to assess different surface coverage scenarios considering increments of forest cover along to the basin watercourses. The scenarios were compared with the current condition of the basin in terms of annual mean streamflow, annual maximum daily streamflow, and frequency of occurrence of very high and very low flow extremes. The simulations indicate a reduction in the annual mean streamflow rate due to the increase of the cover forest; reduction of annual maximum daily streamflow due to the increase in forest cover. Extreme frequency analysis indicates that increasing forest cover promotes a decrease in very high flow events and an increase in very low flow events during the rainy months of the basin (October to March), however, in the dry months (especially in August) the occurrence of very high flow events increases while very low flow events decrease. These results indicate that although on average and during the rainy season forest cover negatively affects surface water availability in the driest months, when water resources are scarcer, increased forest cover is beneficial for water availability in the basin.